Locked-in Syndrome in a Young Patient Due to SARS-CoV-2: A Case Report - Sattar, Saud Bin Abdul; Iqbal, Qasim Zafar; Haider, Muhammad Adnan; Zia, Zeeshan; Niazi, Muhammad Raphay Khan; Hanif, Muhammad; Ali, Mukarram Jamat; Khan, Muhammad Aslam (Frontiers in Medicine, 2020)
Coronavirus disease 2019 (COVID-19), apart from commonly involving the respiratory system, has its impact on the central nervous system, with a wide spectrum of clinical presentations ranging from headaches to ischemic strokes. The ongoing research regarding this novel disease has found that there is a very high prevalence of thrombotic episodes especially in critically ill patients when compared to severe presentation of other viral illnesses. This COVID-19-associated coagulopathy has a very complex etiology with the ability to form thrombus in arteries, veins, and microvasculatures of different organs. We present a unique case of a young woman with underlying COVID-19 who unfortunately developed locked-in syndrome due to bilateral pontine infarction during the course of her illness.